Updated Common Evaluation Framework For IMF Capacity Development And Guidance Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
This document updates the Common Evaluation Framework (CEF) for the Fund's capacity development (CD) activities and provides practical guidance on its implementation. Since its adoption, the Fund has made progress in implementing the CEF. However, areas for improvement remain. The document aims to address these areas, drawing on lessons from experience with evaluations since the CEF's adoption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Donor-Mandated Evaluation; Evaluation Manager; Evaluation Team; PP; Project Evaluation Section